PEMIKIRAN HUKUM MUSLIM DI INDONESIA MODERN - Zhafiri Muhammad, Hasman; Nur Afida, Herlina; Yusdani (Sahaja: Journal Sharia and Humanities, 2023)
The largest religion in Indonesia is Islam, where more than 80 percent of the population is Muslim. In the midst of many studies on Indonesian Islam, it turns out that studies or books that specifically study the history of Islamic legal thought in Indonesia, both classical and contemporary, are still rarely found. From this point of view, Feener succeeded in filling the gap in this study. Presents the trajectory and history of the debate on Islamic Law in Indonesia, besides that the understanding provided is very comprehensive regarding the dynamics of modern Indonesia. Modern Indonesia is a period of the 20th century until the end of the New Order rule, which means that this study has existed for a long time, about 110 years or more than 1 century. Then chronologically presents the chapters based on the book that appeared in the hope that the close relationship between the three factors driving the modernization of Islamic legal thought in Indonesia can be more freel studied in depth. The 19th century has brought a new awareness as an alternative to the yellow book hegemony which is already deeply rooted. Awareness that later developed into a reformist school that challenged the authority of Islamic boarding school ulema as translators of Islamic traditions via the yellow book. This new movement, by using technological advances in the print and information fields, makes it easy to access products of new interpretations of religious law. In this case, the invention of the massive printing press made the prints of the thoughts and results of the reformist ulama's fatwas easy to be consumed by the wider community. Obviously, the progress of the print culture here has rivaled the authority of the Islamic boarding school ulema who used to be the sole authority on the interpretation of religious texts.